Momordica charantia for Diabetes: Exploring Mechanisms & Clinical Implications - B. Dharani; A. Suba (Nutrimentum et Curae)
Diabetes Mellitus (DM) is said to be a chronic disorder, known to cause persistent hyperglycemia. This leads to diabetes-related complications like neuropathy, dyslipidemia, nephropathy and retinopathy. Since the incidence and prevalence of diabetes is increasing globally, there is an urgent requirement of adjunct therapies. Recently, Bitter gourd (Momordica charantia) is attaining popularity among clinicians and researchers because of its potential anti-diabetic properties. This is due to its inbuilt bioactive compounds like polypeptide-p, charantin and vicine. The current review examines the mechanisms and possible benefits of bitter gourd in treating diabetes along with its safety profile and efficacy. It was found that the bioactive compound present in M.charantia helps to regulate the blood glucose level by its mechanism like increased insulin release and sensitivity. Also, it exerts anti-oxidant and anti-inflammatory effect in diabetes. This helps to mitigate the diabetes related complications. Despite many evidences, challenges remain in creating a drug profile on standard formulations, optimal dose and its long-term safety. This limits its clinical application.Further well designed and large-scale clinical trials are needed to validate its drug profile, efficacy and safety in treatment of diabetes as an adjunct therapy.